Enhancing livelihood security of Bundelkhand farmers through integrated farming system - Palsaniya, D. R.; Choudhary, Mukesh; Gupta, Gaurendra; Prasad, Mahendra; Mahawer, S. K.; Kumar, Sunil (Indian Farming, 2025)
Bundelkhand, a semi-arid region spanning parts of Uttar Pradesh and Madhya Pradesh in India, is characterized by its challenging agro-climatic conditions. Recurrent droughts, erratic rainfall, and poor soil fertility have long plagued the agricultural productivity of the region. As a result, farmers often face economic instability and food insecurity. To combat these challenges, the implementationof Integrated Farming Systems (IFS) has emerged as a promising strategy. IFS offers a promising approach to enhance the livelihood security of farmers in the Bundelkhand region, which faces challenges like water scarcity, soil degradation, and climate change. By combining diverse agricultural practices, IFS can optimize resource utilization, improve soil health, and increase overall farm productivity.